Compounds containing weak, non-covalent interactions to the metal in the backbone of 1, 1′-bis(phosphino)metallocene ligands. (16th August 2016) - Warnick, Eugene P.; Dupuis, Ryan J.; Piro, Nicholas A.; Scott Kassel, W.; Nataro, Chip
Graphical abstract: Dimers containing 1, 1′-bis(diphenylphosphino)metallocene (dppMc) ligands with the formula [Pd(dppMc)(μ-Cl)]2 +2 (dppMc = dppr, dppo) were prepared and structurally characterized. Compounds [M(dppMc)PPh3 ] 2+ (M = Pd, dppMc = dppo; M = Pt, dppMc = dppf, dppo) containing an interaction between M and the metal of the dppMc ligand were prepared and structurally characterized. Abstract: The reactions of Na[BArF] (BArF = tetrakis(3, 5-bis(trifluoromethyl)phenyl)borate) with a series of [Pd(dpEMc)Cl2 ] (dpEMc = 1, 1′-bis(diphenylphosphino)ruthenocene (dppr), 1, 1′-bis(diphenylphosphino)osmocene (dppo) or 1, 1′-bis(diphenylarsino)ferrocene (dpaf)) compounds were examined. The reaction of Na[BArF] with [Pd(dppMc)Cl2 ] (dppMc = dppr or dppo) resulted in the formation of the corresponding chloride-bridged dimers, [Pd(dppMc)(μ-Cl)]2 2+, which were structurally characterized. However, these dimers appear to be unstable in CH2 Cl2 and partially (Ru) or fully (Os) convert into the corresponding monomers, [Pd(dppMc)Cl] +, which are proposed to have a weak, non-covalent M–Pd (M = Ru or Os) interaction. Similar compounds, [Pd(dppo)PPh3 ] 2+ and [Pt(dppMc)PPh3 ] 2+ (M = Fe (1, 1′-bis(diphenylphosphino)ferrocene (dppf)) or Os (dppo)), were also prepared and structurally characterized. These compound also exhibit weak, non-covalent M–Pd/Pt interactions. In addition, the electrochemical properties of these compounds were examined by cyclic voltammetry.